Study about conditions of environment sanitation in Kenagarian Air Haji discrict of Linggo Sari Baganti South of Pesisir - Putri, Yaspina D.; Erita, Yeni; Nefilinda, Nefilinda (Pendidikan Geografi, 2013)
Environmental can affect public health. Many aspects of human are influenced by environmental conditions. Sanitation facilities include ventilation, temperature, humidity, occupancy density, delighting, building construction, waste disposal facilities, human waste disposal facilities and water supply. The presence of disease in the community appear Kenagarian Air Haji Linggo Sari  Baganti. One of which is influenced by the management of unimproved sanitation. its  happens because the result of poor management of environmental sanitation. This research aims to determine the condition of the family latrine, garbage disposal conditions of families and family wastewater discharge conditions in Kenagarian air haji District of LinggoSari BagantiSouthof Pesisir.This research is descriptive, the location of the research conducted in Kenagarian air haji District of  Linggo Haji Sari Baganti south of Persisir . The samples used were 93 head of Family Data available in Kenagarian Air Haji .             The survey results revealed that the total TCR for the provision of household toilets which amounted to 76.2 % of respondents entry criteria to the criteria of both the family and concluded the provision of latrines in Kenagarian Air Haji District of  Linggo Sari Baganti south of Persisir .TCR to total garbage disposal amounted to 66.26 % where the criteria for entry to the respondents sufficient criteria and concluded in the family garbage disposal Kenagarian air haji District of  Linggo Sari Baganti South of  Pesisir very well . Total TCR for the disposal of waste water which is equal to 73.66 % of respondents entered criteria to both criteria and concluded the disposal of wastewater family in Kenagarian Air Haji District of  Linggo Haji Sari Baganti South of  Pesisir .